Financial Planning and Saving Behavior: Evidence from Accounting Respondents - N.Heriyah; Neng Mesa (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to analyze the effect of financial planning on saving behavior among accounting-background respondents within the productive age range of 25–45 years. The research method employs a quantitative approach using multiple linear regression analysis. Data were collected through questionnaires distributed to 120 respondents. Classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation, were conducted to ensure the validity of the model. The results indicate that financial planning has a significant influence on saving behavior. The t-test shows that the financial planning variable has a positive and significant effect, the F-test confirms that the regression model is feasible, and the coefficient of determination (R²) of 0.62 suggests that 62% of the variation in saving behavior can be explained by financial planning. These findings highlight the importance of financial literacy and planning in enhancing saving habits among individuals in the productive age group.